2003
DOI: 10.1161/01.res.0000057755.02845.f9
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transfer of Extracellular Superoxide Dismutase Reduces Arterial Pressure in Spontaneously Hypertensive Rats

Abstract: Abstract-Oxidative stress may contribute to hypertension. The goals of this study were to determine whether extracellular superoxide dismutase (ECSOD) reduces arterial pressure in spontaneously hypertensive rats (SHR) and whether its heparin-binding domain (HBD), which is responsible for cellular binding, is necessary for the function of ECSOD. Three days after intravenous injection of an adenoviral vector expressing human ECSOD (AdECSOD), mean arterial pressure (MAP) decreased from 165Ϯ4 mm Hg (meanϮSE, nϭ7) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
130
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(136 citation statements)
references
References 59 publications
(63 reference statements)
5
130
1
Order By: Relevance
“…Results of gene transfer in the present study suggest that in vivo administration of ECSOD with fully active binding capacity may afford protection against vascular dysfunction produced by endotoxin. Based on effects of gene transfer of ECSOD in previous studies (9,12) of hypertension in rats and subarachnoid hemorrhage in rabbits and our present studies, we think it is likely that administration of exogenous SOD, that can bind to blood vessels, may prove to be beneficial in settings other than acute inflammation, such as atherosclerosis and diabetes, in which vascular superoxide is elevated.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Results of gene transfer in the present study suggest that in vivo administration of ECSOD with fully active binding capacity may afford protection against vascular dysfunction produced by endotoxin. Based on effects of gene transfer of ECSOD in previous studies (9,12) of hypertension in rats and subarachnoid hemorrhage in rabbits and our present studies, we think it is likely that administration of exogenous SOD, that can bind to blood vessels, may prove to be beneficial in settings other than acute inflammation, such as atherosclerosis and diabetes, in which vascular superoxide is elevated.…”
Section: Discussionmentioning
confidence: 58%
“…In a previous study (9) using gene transfer in vivo in rats, ECSOD activity was elevated in plasma after either AdECSOD or AdECSOD-HBD. Based on immunohistochemistry studies, however, ECSOD protein was found bound to endothelium and vascular muscle only after gene transfer of AdECSOD but not AdECSOD-HBD (9). Thus the HBD is critical for localization of ECSOD to the vascular wall.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Increased content of superoxide radical (O 2 ¯) was noted in the arteries of spontaneously hypertensive rats; in this case genetic transfer of EC-SOD ameliorated endothelium function and decreased the arterial pressure [16]. Thus, interaction of O 2 ¯ with NO should primary have place in extracellular space [17].…”
Section: Extracellular Superoxide Dismutasementioning
confidence: 99%